O ensino técnico no MST: o caso do Curso Técnico em Agropecuária com habilitação em Agroecologia do Instituto Educar, Pontão, RS - Fagundes, Luciele Alves (2012)
This study investigates about technical education in the Landless Rural Workers Movement (MST in Portuguese) by focusing on the Agropecuary Technical Course specialized in Agroecology offered by Educar Institute, which is located in Pontão, in the north of Rio Grande do Sul State. This research aims to understand the educational processes promoted by the technical education of the MST. The same way, this study tries to comprehend how the MST congregates the technical education with a popular education purpose; observe the articulation of high school and technical education; and, finally, get to know and describe the management and physical structure of the school. This investigation consists on a study case, under a qualitative approach, being characterized as a descriptive research. Among the contributions brought up to discussion, it is highlighted the school organization based on the Escola Comuna principles, besides the unique experience in education promoted by the MST. Although it still presents characteristics of traditional education, it is advancing towards education. Moreover, the rural education theme is emphasized, since the purpose of the Movement is based on its principles, trying to guarantee education about and in the rural area for the rural population which continues to be left out from public policies. It is also emphasized the objective of educating not only technicians in agroecology, but also militants who search to accomplish their demands in the settlements. Thus, the educational process triggered by the MST remains a differentiated, complex and broad process that organizes and territorializes the Movement, as well as serves as an example to the Brazilian society.